Randomized clinical trial of duct-to-mucosa pancreaticogastrostomy versus handsewn closure after distal pancreatectomy. Issue 5 (23rd January 2017) - Uemura, K; Satoi, S; Motoi, F; Kwon, M; Unno, M; Murakami, Y
Abstract: Background: Postoperative pancreatic fistula (POPF) remains a major cause of morbidity after distal pancreatectomy. The aim of this study was to investigate whether duct-to-mucosa pancreaticogastrostomy of the pancreatic stump decreased clinical POPF formation compared with handsewn closure after distal pancreatectomy. Methods: This multicentre RCT was performed between April 2012 and June 2014. Patients undergoing distal pancreatectomy were assigned randomly to either duct-to-mucosa pancreaticogastrostomy or handsewn closure. The primary endpoint was the incidence of clinical POPF. Secondary endpoints were rates of other complications and length of hospital stay. Results: Some 80 patients were randomized, and 73 patients were evaluated in an intention-to-treat analysis: 36 in the pancreaticogastrostomy group and 37 in the handsewn closure group. The duration of operation was significantly longer in the pancreaticogastrostomy group than in the handsewn closure group (mean 268 versus 197 min respectively; P < 0·001). The incidence of clinical POPF did not differ between groups (7 of 36 versus 7 of 37; odds ratio (OR) 1·03, 95 per cent c.i. 0·32 to 3·10; P = 1·000). The rate of intra-abdominal fluid collection was significantly lower in the pancreaticogastrostomy group (6 of 36 versus 21 of 37; OR 0·15, 0·05 to 0·45; P < 0·001). There were no statistically significant differences in the rates of other complications or length of hospital stay. Conclusion: Duct-to-mucosa pancreaticogastrostomy did not reduce the incidence of clinical POPF compared with handsewn closure of the pancreatic stump after distal pancreatectomy. Registration number UMIN000007426 (http://www.umin.ac.jp ). Abstract : Pancreatic fistula rate similar